Signs of media logic - Brants, Kees (Javnost (Ljubljana), 2006)
On the basis of three elections, covering a period of fifty years, the authorsaim at testing the increasingly popular hypothesis that political communication is driven by media logic and by political and media system characteristics. In short: sooner or later, the modes and styles of American media will appear in Europe too. The complex and volatile relationship betweenmedia and politics in the Netherlands in the last half-century does show some, although not uni-linear signs of media logic. The strength of a public service tradition and a political culture of nonadversariality, however, seem to have stopped the developments short of a political communication style which is characterised by performance driven campaigning, horse race and poll driven reporting, orientation on the public as consumers, journalistic dominance, agenda setting and cynicism.
Keywords: mass media; množični mediji; javnost; obveščanje; informiranje; communication; komuniciranje; objektivnost; politične razmere; Nizozemska